Governance of Nemberala Coastal Natural Resources in Rote District Ndao - Tiran, Rex; Muskanan, Frans W.; Ndoda, Philips Y. N.; Sinu, Ambrosius Dedi A. (GoAcademica Research & Publishing, 2024)
This study focuses on the governance of non-extractive natural resources on the Nemberala coast. More specifically, this study aims to trace the access mechanism and power relations of foreign capitalists and the government in the development of resorts, villas and cafes in the Nemberala coastal area, Rote Ndao Regency as a means of supporting tourism and what the implications are for local communities. This study uses two access mechanism approaches, Nency Peluso's Access theory (1992) and Nanang's (2021) elements of political analysis of natural resources as units of analysis. This study uses a single case study strategy with a qualitative inductive research approach. This study found that discourse and material power can change the composition of power and values ​​in an area in the form of domination as an exercise of power. Apart from that, this study found that material power operates at a closed spatial level so that in the land acquisition process on the Nemberala coast unconstitutional practices occur. The study of natural resource governance shows that there are three key actors in the governance of Nemberala's coastal natural resources, namely the government, foreign capitalists and land-owning communities. On the other hand, capitalization, privatization and commodification arise due to the globalization of the tourism market or the internationalization of tourism. Placing tourism in the capitalist space means that natural resource management will discuss who gets what, where it gets it, and how it gets it.